Representation of material balance for fractional crystallization of reciprocal salt pair Systems: KNO3 production case study (Chemical Engineering Research Bulletin, 2010)
In this paper, determination of material balance for reciprocal salt pair systems is considered and special case of KNO3 production is solved. A scheme is presented for calculation of material balance which is based on the conservation of ions and water. Material balance requires equilibrium composition and phase diagram of solid-liquid equilibria that is calculated by extended UNIQUAC thermodynamic model.Keywords: Fractional crystallization; KNO3 production; Material balance; Reciprocal Salt Pair systemsDOI = 10.3329/cerb.v14i2.5542Chemical Engineering Research Bulletin 14 (2010) 103-109